2011
DOI: 10.4314/ijbcs.v4i5.65558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxicity of a methanolic total extract of <i>Mitragyna ciliata</i> a natural anti-malaric

Abstract: Mitragyna ciliata (MYTA) is a Rubiaceae used in traditional medicine to treat malaria. Total methanolic extract of MYTA made was used for toxicological studies on laboratory mice and rats. The extract of MYTA was administered intraperitoneally. The doses ranged from 0 to 4000 mg/kg body weight (bw) (i.e., 0, 250, 500, 1000, 2000 and 4000 mg/kg bw) for acute toxicity, and from 0 to 475 mg/kg body weight (bw) (i.e., 0, 125, 250 and 475 mg/kg bw) for subacute toxicity studies. Following administration of high dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Results in Laper and Placo did not differ significantly (P>0.05). These results are similar to those obtained by Bidie et al (2010) [33]. Indeed, these authors found an IC 50 of 7.5 μg / mL and 10.5 μg / mL in the extracts of Trichilia prieuriana and Mitragyna ciliata respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results in Laper and Placo did not differ significantly (P>0.05). These results are similar to those obtained by Bidie et al (2010) [33]. Indeed, these authors found an IC 50 of 7.5 μg / mL and 10.5 μg / mL in the extracts of Trichilia prieuriana and Mitragyna ciliata respectively.…”
Section: Discussionsupporting
confidence: 89%
“…50 g of drug powder were homogenized in 1.5 L of pure methanol in a mixer; the following steps were identical to those of the aqueous extraction above [26].…”
Section: Methanolic Extractionmentioning
confidence: 99%
“…The method of Behrens and Karber (1983) was used for the calculation of the LD 50 which, generally, reflects the lethal nature of a substance (Bidie et al, 2010). The LD 50 values of H. madagascariensis extract were 11.6 g/kg and 13.2 g/kg for female and male mice respectively, whereas those of E. prostrata extract were 23.2 g/kg and 26.4 g/kg for female and male mice, respectively.…”
Section: Acute Toxicitymentioning
confidence: 99%
“…Hepatic necrosis and oxidation have always been assessed through the measurement of markers like ASAT and ALAT (Tala et al, 2015;Olaleye et al, 2014;Bidie et al, 2010). In case of hepatotoxicity, the ALAT and ASAT increased simultaneously in the serum (Tala et al, 2015).…”
Section: Toxicity Testmentioning
confidence: 99%